A high-performance refractive index sensor based on a triangular-lattice photonic crystal with defect and surface modes. (3rd December 2019) - Cui, Ting; Liu, Xing; Zhou, Lin; Feng, Shuai; Chen, Xiao; Guo, Honglian; Li, Chuanbo; Wang, Yiquan
Abstract: The refractive index sensing capabilities of a 2D triangular-lattice photonic crystal (PhC) with defective and surface modes are studied. These are composed of silicon columns arranged in a liquid environment. Through changing the rods' shape on the PhC's surface from a circle to an ellipse and optimizing the sizes of two adjacent ellipses, the surface localized mode can be generated. Combining the central defective mode with surface modes, an ultra-small three-working-wavelength PhC refractive index sensor is proposed. The shift of the resonant wavelengths influenced by the slight alteration of the protein's thickness attached by the special rods is studied, and it is found that a minimum alteration of the protein's thickness of about 4 nm can be distinguished, and a maximum refractive index sensitivity of 0.516 is obtained. Three kinds of analytes can be detected in real-time and at the same time, which are bounded around the input/output surfaces and the central rods through biological specific binding.